Monitoring by the Ombudsman of Ukraine for compliance with the labor rights of civilians who have disappeared under special circumstances - Yu. F. Ivanov; M. V. Ivanova (Bulletin of Kharkiv National University of Internal Affairs)
The results of the monitoring of the Commissioner for Human Rights of the Verkhovna Rada of Ukraine regarding compliance with the labor rights of persons with the status of persons who have disappeared under special circumstances are presented. The actuality of the topic is due to the fact that ensuring compliance with the constitutional rights of citizens, primarily citizens who need additional social protection, is a priority of the state. Attention was drawn to the fact that the observance of such rights, especially in the conditions of martial law, is an important aspect of state policy. The purpose of the article is to analyze the legislation regulating compliance with the labor rights of civilian employees who are missing due to military aggression by the russian federation. Achieving the outlined goal became possible thanks to the use of a complex of methods of scientific knowledge: dialectical, comparative-legal, formal-logical, systemic-structural.